Preliminary assessment of air pollutant sources identification at selected monitoring stations in Klang Valley, Malaysia - Mohamad, Nur Diyana; Ash’aari, Zulfa Hanan; Othman, Melawani (Elsevier, 2015)
This study aims to carry out a preliminary assessment for pollutant sources identification using a statistical approach consisting of analysis of variance (ANOVA) and principal component analysis (PCA). Substantially, both statistical methods were applied to assess whether there was a significant difference between sites, and also to identify pollution sources for each monitoring site. Results from PCA reveal that the most significant factor loadings were dominantly covered by nitrogen dioxide (NO2), carbon monoxide (CO) and particulate matter (PM10) emission for most of the sites, followed by other major air pollutant contributors, namely, sulphur dioxide (SO2) and ozone (O3)